Blended surface self-repairing and reinforcing material as well as preparation method and application method thereof
By preparing blended surface self-repair and reinforcement materials, using specific proportions of components and process treatment, the shortcomings of existing permeable crystalline materials in waterproofing and concrete reinforcement are solved, and efficient, economical and environmentally friendly concrete restoration and reinforcement effects are achieved.
Patent Information
- Application Number
- CN202411632821.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-25
AI Technical Summary
The existing permeable crystalline materials have poor stability, insufficient waterproof and seepage resistance and concrete reinforcement, complex construction operations, high cost and potential environmental hazards, and lack an economical and feasible solution with a long service life.
Using blended surface self-healing and reinforcement materials, materials with good adhesion and permeability are prepared by mixing complexing catalyst, water retention enhancer, inorganic silicone material, water-soluble silicone material with water in a specific ratio, and heating and stirring treatment.
The material exhibits good adhesion and permeability on both the surface and interior of the concrete, can effectively repair cracks, strengthen the overall strength and durability of the concrete, reduce the construction and maintenance cycle, and is also economical and environmentally friendly.
Smart Images

Figure CN119684907A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of material technology, and more specifically, to a blended surface self-repairing reinforcement material and a preparation method and an application method thereof. Background Art
[0002] Permeable crystalline material is a liquid substance used for building structural reinforcement and waterproofing. The principle of reinforcement and waterproofing of permeable crystalline material is that when the material encounters water, the active substances and catalysts in the material dissolve in water and penetrate into the concrete structure with water as a carrier. In the process of penetration and movement, the active substances in the material react chemically with anion groups such as calcium ions, silicate ions, sulfate ions, etc. in the pores inside the structure, and generate a certain amount of water-insoluble crystalline substances in the pores. These crystalline substances and hydration products are generated in the pores and gaps along the way, so that the gaps in these structures are filled and blocked, thereby blocking these channels that originally belonged to water seepage and migration, effectively reducing the amount of water seepage in the structure, improving the waterproof ability of the structure, and reinforcing the original structure at the same time.
[0003] Traditional cement-based permeable crystallization materials have good cementitiousness, high stone strength, convenient slurry preparation, economy and environmental protection, but the slurry has poor stability, easy precipitation and water separation, and insufficient waterproof and anti-seepage capabilities. Compared with cement slurry, cement-water glass permeable crystallization liquid has improved anti-seepage ability, shortened solidification time and improved fluidity, but it is a two-component material with complex construction operations. At the same time, the solidified slurry has insufficient strength and toughness, low durability and is prone to brittle failure. Although chemical permeable crystallization materials have excellent waterproof and anti-seepage properties, they have high material costs, complex preparation processes, and may cause harm to the environment.
[0004] In summary, there is currently a lack of an economically feasible solution that has good concrete repair and reinforcement effects, long service life, and waterproof and anti-seepage effects. Summary of the invention
[0005] In view of the above problems, the purpose of the present invention is to provide a blended surface self-repairing reinforcement material and a preparation method and an application method thereof. The prepared blended surface self-repairing reinforcement material has excellent adhesion and anti-permeability, good repair and reinforcement effect, long service life, simple preparation, strong economy, and can better solve the problems existing in the prior art.
[0006] The present invention provides a blended surface self-repairing reinforcement material, comprising the following components in parts by volume:
[0007] 0.1-1 parts of complex catalyst, 0.1-5 parts of water retention enhancer, 0.1-1 parts of inorganic silicon material, 0.1-1 parts of water-soluble organic silicon material, 90-99 parts of water.
[0008] In addition, a preferred solution is that the complex catalyst is any one of sodium acetate, sodium nitrate, sodium sulfate, and magnesium fluoride silicate, or at least two of them mixed in any proportion.
[0009] In addition, a preferred solution is that the water retention enhancer is any one of hydroxypropyl methylcellulose, sodium carboxymethyl cellulose, ethylenediaminetetraacetic acid, sodium polyacrylate, or at least two of them mixed in any proportion.
[0010] In addition, a preferred solution is that the inorganic silicon material is any one of sodium silicate, potassium silicate, calcium silicate, and lithium silicate, or at least two of them mixed in any proportion.
[0011] In addition, a preferred solution is that the water-soluble organic silicon material is any one of sodium methyl silicate, water-soluble siloxane, polydimethylsiloxane, methyl silicone oil, or at least two of them mixed in any proportion.
[0012] The present invention also provides a method for preparing the above-mentioned blended surface self-repairing reinforcement material, comprising the following steps:
[0013] The complex catalyst, the water retention enhancer, the inorganic silicon material, the water-soluble organic silicon material and water are mixed according to a proportion to obtain a mixed solution;
[0014] The mixed liquid is heated and stirred to make the mixed liquid uniformly mixed, and the temperature is 30-40° C. to obtain a blended surface self-repairing reinforcement material.
[0015] In addition, a preferred solution is that during the heating and stirring of the mixed liquid to make the mixed liquid evenly mixed and the temperature of the mixed liquid is 30-40°C to obtain the blended surface self-repair reinforcement material, the mixed liquid is heated and stirred in a constant temperature water bath with a stirring function.
[0016] In addition, a preferred solution is that when the mixed liquid is heated and stirred in a constant temperature water bath with a stirring function, the rotation speed is set to 200-1000 r / min, and the uniform stirring time is at least 30 min.
[0017] The present invention also provides an application method of the above-mentioned blended surface self-repairing reinforcement material, comprising the following steps:
[0018] Cleaning the surface of the concrete test block, determining the location of the cracks on the surface of the concrete test block and measuring the size of the cracks;
[0019] Determine the amount of the blended surface self-repairing reinforcement material according to the crack position and crack size of the concrete test block, and apply the blended surface self-repairing reinforcement material to the cracks on the surface of the concrete test block based on the amount;
[0020] After the blended surface self-repairing reinforcement material at the crack is completely dry, the surface cracks of the concrete test block are repaired.
[0021] In addition, a preferred solution is that after the mixed surface self-repairing reinforcement material at the crack is completely dried to complete the repair of the surface cracks of the concrete test block, it also includes:
[0022] After the blended surface self-repairing reinforcement material at the crack is completely dry, the blended surface self-repairing reinforcement material is repeatedly applied to the crack at least three times, and each time the blended surface self-repairing reinforcement material is applied, the blended surface self-repairing reinforcement material is applied after the previous blended surface self-repairing reinforcement material is completely air-dried.
[0023] As can be seen from the above technical scheme, the blended surface self-repairing reinforcement material provided by the present invention and its preparation method and application method, by using inorganic silicon material, water-soluble organosilicon material, water-retaining enhancer and complex catalyst as main raw materials, each raw material has good compatibility with concrete, and low cost, easy to construct, and the above several main raw materials are compounded and used, and the synergistic effect between each other makes the prepared self-repairing reinforcement material not only have good cohesiveness and anti-permeability effect, but also can improve the overall strength, mechanical properties, durability and crack resistance of concrete, so as to play a good self-repairing reinforcement effect on concrete cracks. It is effectively shortened by compounding complex catalyst (containing early strength accelerating coagulation component) to shorten the setting time after construction, accelerate the hardening process, make it harden rapidly while maintaining high strength and excellent bonding performance, and improve the early concrete strength level, thereby significantly reducing construction and maintenance cycle. Compared with traditional materials, the solidification and hardening speed of the present invention is faster, and it also has stronger impermeability. By compounding water-soluble silicone, silicon ions are used to react chemically with inorganic potassium salts to form insoluble and irreversible inorganic substances to fill pores and cracks, thereby improving the strength, waterproofness, durability and self-healing properties of concrete.
[0024] In order to achieve the above and related purposes, one or more aspects of the present invention include the features that will be described in detail later. The following description and the accompanying drawings describe some exemplary aspects of the present invention in detail. However, these aspects indicate only some of the various ways in which the principles of the present invention can be used. In addition, the present invention is intended to include all these aspects and their equivalents. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] By referring to the following description in conjunction with the accompanying drawings, and with a more complete understanding of the present invention, other objects and results of the present invention will become more apparent and easily understood.
[0026] Figure 1 This is a flow chart of a method for preparing a blended surface self-repairing reinforcement material according to an embodiment of the present invention;
[0027] Figure 2 The present invention is a flow chart of an application method of a blended surface self-repairing reinforcement material according to an embodiment of the present invention. DETAILED DESCRIPTION
[0028] In the following description, for the purpose of explanation, numerous specific details are set forth in order to provide a thorough understanding of one or more embodiments. However, it is apparent that these embodiments may also be implemented without these specific details.
[0029] In view of the problems existing in the prior art mentioned above, it is necessary to provide a material with good adhesion and anti-permeability, good effect on repairing and reinforcing concrete cracks, long service life, simple preparation and strong economy. The present invention proposes a blended surface self-repairing reinforcement material and its preparation method and application method.
[0030] The specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.
[0031] In order to illustrate the blended surface self-repairing reinforcement material provided by the present invention and its preparation method and application method, Figure 1 The preparation process of the blended surface self-repairing reinforcement material according to an embodiment of the present invention is shown; Figure 2 The application process of the blended surface self-repairing reinforcement material according to an embodiment of the present invention is shown.
[0032] The blended surface self-repairing reinforcement material provided by the present invention comprises the following components in parts by volume:
[0033] 0.1-1 parts of complex catalyst, 0.1-5 parts of water retention enhancer, 0.1-1 parts of inorganic silicon material, 0.1-1 parts of water-soluble organic silicon material, 90-99 parts of water.
[0034] The self-repairing reinforcement material penetrates into the interior of the concrete. The chemically active substances use water as a carrier and penetrate into the interior of the matrix to promote further hydration of the unhydrated particles in the concrete or undergo a complexation-precipitation reaction with some hydration products to generate water-insoluble products, thereby achieving the repair of cracks.
[0035] Among them, by compounding the complex catalyst, that is, containing the early strength accelerating component, the setting time after construction can be effectively shortened, the hardening process can be accelerated, and the hardening can be made to maintain high strength and excellent bonding performance while hardening quickly, and the early concrete strength level can be improved, thereby significantly reducing the construction and maintenance cycle. Compared with traditional materials, the solidification and hardening speed is faster, and at the same time it has stronger anti-permeability performance. By compounding water-soluble organic silicon materials, silicon ions react chemically with inorganic potassium salts to form insoluble irreversible inorganic substances to fill pores and cracks, thereby improving the strength, waterproof performance, durability and self-healing properties of concrete. By using inorganic silicon materials, water-soluble organic silicon materials, water-retention enhancers and complex catalysts as the main raw materials, each raw material has good compatibility with concrete, low cost, and easy construction. The above main raw materials are compounded and used, and the synergistic effect between each other makes the prepared self-repairing reinforcement material not only have good bonding and anti-permeability effects, but also can improve the overall strength, mechanical properties, durability and crack resistance of concrete, thereby playing a good self-repairing reinforcement role on concrete cracks.
[0036] As a preferred embodiment of the present invention, the complex catalyst is any one of sodium acetate, sodium nitrate, sodium sulfate, and magnesium fluoride silicate, or at least two of them mixed in any proportion.
[0037] It should be noted that the water retention enhancer is preferably, but not limited to, any one of hydroxypropyl methylcellulose, sodium carboxymethyl cellulose, ethylenediaminetetraacetic acid, sodium polyacrylate, or at least two of them mixed in any proportion.
[0038] As a preferred embodiment of the present invention, the inorganic silicon material is any one of sodium silicate, potassium silicate, calcium silicate and lithium silicate, or at least two of them mixed in any proportion.
[0039] It should be noted that the inorganic silicon material is preferably but not limited to any one of sodium silicate, potassium silicate, calcium silicate, and lithium silicate, or at least two of them mixed in any proportion.
[0040] As a preferred embodiment of the present invention, the water-soluble organic silicon material is any one of sodium methyl silicate, water-soluble siloxane, polydimethylsiloxane, methyl silicone oil, or at least two of them mixed in any proportion.
[0041] It should be noted that the water-soluble organic silicon material is preferably but not limited to any one of sodium methyl silicate, water-soluble siloxane, polydimethylsiloxane, methyl silicone oil, or at least two of them mixed in any proportion.
[0042] like Figure 1 As shown, the preparation method of the blended surface self-repairing reinforcement material provided by the present invention comprises the following steps:
[0043] Step S1, mixing a complex catalyst, a water retention enhancer, an inorganic silicon material, a water-soluble organic silicon material, and water according to a ratio to obtain a mixed solution;
[0044] Step S2, heating and stirring the mixed liquid to make the mixed liquid evenly mixed, and the temperature is 30-40° C. to obtain a blended surface self-repairing reinforcement material.
[0045] As a preferred embodiment of the present invention, the mixed liquid is heated and stirred to make the mixed liquid uniformly mixed, and the temperature is 30-40° C. to obtain the blended surface self-repairing reinforcement material.
[0046] The mixed solution is heated and stirred in a constant temperature water bath with a stirring function.
[0047] As a preferred embodiment of the present invention, when the mixed liquid is heated and stirred in a constant temperature water bath with a stirring function, the rotation speed is set to 200-1000 r / min, and the uniform stirring time is at least 30 min.
[0048] Specifically, heating and stirring the mixed liquid in a constant temperature water bath with a stirring function can further simplify the preparation process and make the uniformity of heating and stirring of the mixed liquid easier to control, thereby making the prepared self-healing reinforcement material more effective.
[0049] like Figure 2 As shown, the application method of the blended surface self-repairing reinforcement material provided by the present invention comprises the following steps:
[0050] Step A1, clean the surface of the concrete test block, determine the crack position on the surface of the concrete test block and measure the crack size;
[0051] Step A2: determining the amount of the blended surface self-repairing reinforcement material according to the crack position and crack size of the concrete test block, and applying the blended surface self-repairing reinforcement material to the cracks on the surface of the concrete test block based on the amount;
[0052] Step A3: After the blended surface self-repairing reinforcement material at the crack is completely dry, the surface cracks of the concrete test block are repaired.
[0053] As a preferred embodiment of the present invention, after the blended surface self-repairing reinforcement material at the crack is completely dried to complete the repair of the surface cracks of the concrete test block, the method further comprises:
[0054] After the blended surface self-repairing reinforcement material at the crack is completely dry, repeat brushing the blended surface self-repairing reinforcement material at the crack for at least three times, and each time the blended surface self-repairing reinforcement material is brushed, the blended surface self-repairing reinforcement material is completely air-dried.
[0055] Specifically, the crack size includes length, width and depth. When the solution material is completely dry, repeat the application again to ensure the self-repair and reinforcement effect of the cracks. It is preferred to repeat the application at least three times. The material generally takes 7 days to air dry and can play a role in reinforcement and waterproofing.
[0056] In order to verify the technical effects of the blended surface self-repairing reinforcement material and its preparation method and application method provided by the present invention, the following specific examples are provided.
[0057] Example 1
[0058] The self-healing reinforcement material is prepared according to the following components by volume:
[0059] 0.2 parts of magnesium fluoride silicate, 0.05 parts of ethylenediaminetetraacetic acid, 0.1 parts of potassium silicate, 0.1 parts of sodium methyl silicate, 99 parts of water.
[0060] Step S1, mixing magnesium fluoride silicate, ethylenediaminetetraacetic acid, potassium silicate, sodium methyl silicate and water to obtain a mixed solution;
[0061] Step S2, placing the mixed liquid in a constant temperature water bath with a stirring function for heating, setting the temperature to 35° C., setting the rotation speed to 500 r / min, and stirring at a constant speed for 30 minutes to obtain a blended surface self-repairing reinforcement material.
[0062] Clean the surface of the concrete test block and measure the location, length and depth of the concrete cracks;
[0063] Use the above-mentioned blended surface self-repairing reinforcement material to brush the cracks on the surface of the concrete test block. When the material is completely dry, repeat the brushing again. In order to ensure the crack self-repairing reinforcement effect, this operation is repeated three times;
[0064] After waiting for 7 days to completely air dry, the strength of the concrete specimens at the cracks was tested and the microstructure was inspected.
[0065] Example 2
[0066] The self-healing reinforcement material is prepared according to the following components by volume:
[0067] 0.4 parts of sodium acetate, 0.1 parts of sodium carboxymethyl cellulose, 0.3 parts of potassium silicate, 0.2 parts of water-soluble silicone, and 99 parts of water.
[0068] Step S1, mixing sodium acetate, sodium carboxymethyl cellulose, potassium silicate, water-soluble siloxane and water to obtain a mixed solution;
[0069] Step S2, placing the mixed liquid in a constant temperature water bath with a stirring function for heating, setting the temperature to 35° C., setting the rotation speed to 500 r / min, and stirring at a constant speed for 30 minutes to obtain a blended surface self-repairing reinforcement material.
[0070] Clean the surface of the concrete test block and measure the location, length and depth of the concrete cracks;
[0071] Use the above-mentioned blended surface self-repairing reinforcement material to brush the cracks on the surface of the concrete test block. When the material is completely dry, repeat the brushing again. In order to ensure the crack self-repairing reinforcement effect, this operation is repeated three times;
[0072] After waiting for 7 days to completely air dry, the strength of the concrete specimens at the cracks was tested and the microstructure was inspected.
[0073] Example 3
[0074] The self-healing reinforcement material is prepared according to the following components by volume:
[0075] 0.6 parts of magnesium fluoride silicate, 0.15 parts of ethylenediaminetetraacetic acid, 0.5 parts of sodium silicate, 0.3 parts of water-soluble siloxane, and 98 parts of water.
[0076] Step S1, mixing magnesium fluoride silicate, ethylenediaminetetraacetic acid, sodium silicate, water-soluble siloxane and water to obtain a mixed solution;
[0077] Step S2, placing the mixed liquid in a constant temperature water bath with a stirring function for heating, setting the temperature to 35° C., setting the rotation speed to 500 r / min, and stirring at a constant speed for 30 minutes to obtain a blended surface self-repairing reinforcement material.
[0078] Clean the surface of the concrete test block and measure the location, length and depth of the concrete cracks;
[0079] Use the above-mentioned blended surface self-repairing reinforcement material to brush the cracks on the surface of the concrete test block. When the material is completely dry, repeat the brushing again. In order to ensure the crack self-repairing reinforcement effect, this operation is repeated three times;
[0080] After waiting for 7 days to completely air dry, the strength of the concrete specimens at the cracks was tested and the microstructure was inspected.
[0081] Example 4
[0082] The self-healing reinforcement material is prepared according to the following components by volume:
[0083] 0.8 parts of magnesium fluoride silicate, 0.2 parts of ethylenediaminetetraacetic acid, 0.7 parts of potassium silicate, 0.4 parts of sodium methyl silicate, 97 parts of water.
[0084] Step S1, mixing magnesium fluoride silicate, ethylenediaminetetraacetic acid, potassium silicate, sodium methyl silicate and water to obtain a mixed solution;
[0085] Step S2, placing the mixed liquid in a constant temperature water bath with a stirring function for heating, setting the temperature to 35° C., setting the rotation speed to 500 r / min, and stirring at a constant speed for 30 minutes to obtain a blended surface self-repairing reinforcement material.
[0086] Clean the surface of the concrete test block and measure the location, length and depth of the concrete cracks;
[0087] Use the above-mentioned blended surface self-repairing reinforcement material to brush the cracks on the surface of the concrete test block. When the material is completely dry, repeat the brushing again. In order to ensure the crack self-repairing reinforcement effect, this operation is repeated three times;
[0088] After waiting for 7 days to completely air dry, the strength of the concrete specimens at the cracks was tested and the microstructure was inspected.
[0089] Example 5
[0090] The self-healing reinforcement material is prepared according to the following components by volume:
[0091] 1 part of magnesium fluoride silicate, 0.25 parts of hydroxypropyl methylcellulose, 0.9 parts of potassium silicate, 0.5 parts of polydimethylsiloxane, 95 parts of water.
[0092] Step S1, mixing magnesium fluoride silicate, hydroxypropyl methylcellulose, potassium silicate, polydimethylsiloxane and water to obtain a mixed solution;
[0093] Step S2, placing the mixed liquid in a constant temperature water bath with a stirring function for heating, setting the temperature to 35° C., setting the rotation speed to 500 r / min, and stirring at a constant speed for 30 minutes to obtain a blended surface self-repairing reinforcement material.
[0094] Clean the surface of the concrete test block and measure the location, length and depth of the concrete cracks;
[0095] Use the above-mentioned blended surface self-repairing reinforcement material to brush the cracks on the surface of the concrete test block. When the material is completely dry, repeat the brushing again. In order to ensure the crack self-repairing reinforcement effect, this operation is repeated three times;
[0096] After waiting for 7 days to completely air dry, the strength of the concrete specimens at the cracks was tested and the microstructure was inspected.
[0097] Table 1 shows the comprehensive performance of the blended surface self-repairing reinforcement material application measured in the above Examples 1-5.
[0098] Example Compressive strength / MPa Flexural strength / MPa Bond strength / MPa Penetration depth / mm 1 52.3 36.2 22.7 42.3 2 51.6 35.8 27.4 40.7 3 53.4 37.9 31.2 33.6 4 54.8 37.8 35.4 29.4 5 53.6 34.2 33.8 36.6
[0099] The blended surface self-repairing reinforcement material provided by the present invention includes inorganic silicon material, water-soluble organic silicon material, water-retention enhancer and complex catalyst as main components. The material is applied to the concrete surface to produce a synergistic effect, enhancing the waterproofness, durability and strength of concrete and concrete cracks. Among them, the bonding strength of Example 4 reaches 35.4MPa. After being immersed in water for a long time, all the above embodiments show a certain penetration depth and finally tend to balance. Thanks to the growth of complex crystals in concrete cracks, they can penetrate into the structure. The combination of the material and concrete can form an excellent waterproof system, and make the whole more compact, effectively improving its applicability.
[0100] The above specific embodiments are only used to help understand the method and effects of the present invention. It should be noted that, for those skilled in the art, without departing from the principles of the present invention, several improvements and modifications may be made to the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
[0101] It can be seen from the above specific embodiments that the blended surface self-repairing reinforcement material and its preparation method and application method are based on inorganic silicon material, water-soluble organosilicon material, water-retaining enhancer and complex catalyst as the main raw materials. The compatibility of each raw material with concrete is good, and the cost is low, easy to construct, and the above several main raw materials are compounded and used. The synergistic effect between each other makes the prepared self-repairing reinforcement material not only have good adhesion and anti-permeability, but also can improve the overall strength, mechanical properties, durability and crack resistance of concrete, so as to play a good self-repairing reinforcement effect on concrete cracks. It effectively shortens the setting time after construction and accelerates the hardening process by compounding complex catalyst (containing early strength accelerating coagulation component), so that it can harden rapidly while maintaining high strength and excellent bonding performance, and improves the early concrete strength level, thereby significantly reducing the construction and maintenance cycle. Compared with traditional materials, the solidification and hardening speed of the present invention is faster, and it also has stronger impermeability. By compounding water-soluble silicone, silicon ions are used to react chemically with inorganic potassium salts to form insoluble and irreversible inorganic substances to fill pores and cracks, thereby improving the strength, waterproofness, durability and self-healing properties of concrete.
[0102] As described above with reference to the accompanying drawings, the blended surface self-repairing reinforcement material and its preparation method and application method proposed according to the present invention are described by way of example. However, those skilled in the art should understand that various improvements can be made to the blended surface self-repairing reinforcement material and its preparation method and application method proposed in the present invention without departing from the content of the present invention. Therefore, the protection scope of the present invention should be determined by the content of the attached claims.
Claims
1. A blended surface self-repairing reinforcement material, characterized in that: The following components are included in volume: 0.1-1 parts of complex catalyst, 0.1-5 parts of water retention enhancer, 0.1-1 parts of inorganic silicon material, 0.1-1 parts of water-soluble organic silicon material, 90-99 parts of water.
2. The blended surface self-repairing reinforcement material according to claim 1, characterized in that: The complex catalyst is any one of sodium acetate, sodium nitrate, sodium sulfate, and magnesium fluoride silicate, or at least two of them mixed in any proportion.
3. The blended surface self-repairing reinforcement material according to claim 1, characterized in that: The water retention enhancer is any one of hydroxypropyl methylcellulose, sodium carboxymethyl cellulose, ethylenediaminetetraacetic acid, sodium polyacrylate, or at least two of them mixed in any proportion.
4. The blended surface self-repairing reinforcement material according to claim 1, characterized in that: The inorganic silicon material is any one of sodium silicate, potassium silicate, calcium silicate and lithium silicate, or at least two of them mixed in any proportion.
5. The blended surface self-repairing reinforcement material according to claim 1, characterized in that: The water-soluble organic silicon material is any one of sodium methyl silicate, water-soluble siloxane, polydimethylsiloxane, methyl silicone oil, or at least two of them mixed in any proportion.
6. A method for preparing a blended surface self-repairing reinforcement material according to any one of claims 1 to 5, characterized in that: The steps include: The complex catalyst, the water retention enhancer, the inorganic silicon material, the water-soluble organic silicon material and water are mixed according to a proportion to obtain a mixed solution; The mixed liquid is heated and stirred to make the mixed liquid uniformly mixed, and the temperature is 30-40° C. to obtain a blended surface self-repairing reinforcement material.
7. The method for preparing the blended surface self-repairing reinforcement material according to claim 6, characterized in that: In the process of heating and stirring the mixed solution to make the mixed solution uniform and the temperature of the mixed solution is 30-40° C. to obtain the blended surface self-repairing reinforcement material, The mixed solution is heated and stirred in a constant temperature water bath with a stirring function.
8. The method for preparing the blended surface self-repairing reinforcement material according to claim 7, characterized in that: When the mixed solution is heated and stirred in a constant temperature water bath with a stirring function, the rotation speed is set to 200-1000 r / min, and the uniform stirring time is at least 30 min.
9. A method for applying the blended surface self-repairing reinforcement material according to any one of claims 1 to 5, characterized in that: The steps include: Cleaning the surface of the concrete test block, determining the location of the cracks on the surface of the concrete test block and measuring the size of the cracks; Determine the amount of the blended surface self-repairing reinforcement material according to the crack position and crack size of the concrete test block, and apply the blended surface self-repairing reinforcement material to the cracks on the surface of the concrete test block based on the amount; After the blended surface self-repairing reinforcement material at the crack is completely dry, the surface cracks of the concrete test block are repaired.
10. The application method of the blended surface self-repairing reinforcement material according to claim 9, characterized in that: After the mixed surface self-repairing reinforcement material at the crack is completely dried to complete the repair of the surface cracks of the concrete test block, the method further includes: After the blended surface self-repairing reinforcement material at the crack is completely dry, the blended surface self-repairing reinforcement material is repeatedly applied to the crack at least three times, and each time the blended surface self-repairing reinforcement material is applied, the blended surface self-repairing reinforcement material is applied after the previous blended surface self-repairing reinforcement material is completely air-dried.